2020
DOI: 10.32615/ps.2020.063
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba and Helianthus annuus show different strategies to adjust photosynthesis, leaf water relations, and cell wall composition under water deficit stress

Abstract: Cell wall thickness (Tcw) determines photosynthesis and leaf elasticity. However, only a few studies in angiosperms addressed cell wall composition implication in regulating photosynthesis and leaf water relations through mesophyll conductance (gm) and bulk modulus of elasticity (ε) adjustments, respectively. Thus, we compared the phylogenetically distant Ginkgo biloba L. and Helianthus annuus L. under control and water deprivation to study the relationship between changes in cell wall composition (cellulose, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Although both genotypes presented similar reductions in π o under water shortage conditions, elastic modifications were of higher relevance in the LSL genotype (Figure 1 ). In fact, ε adjustments occurring under water deficit stress are variable (see, for instance, Sobrado & Turner, 1983 ; Lo Gullo & Salleo, 1988 ; Nadal et al., 2020 ; Roig‐Oliver, Bresta, Nadal, et al., 2020 ; Roig‐Oliver, Nadal, Bota, et al., 2020 ; Roig‐Oliver, Nadal, Clemente‐Moreno, et al., 2020 ; Roig‐Oliver, Fullana‐Pericàs, et al., 2021 ), suggesting that they could be species‐dependent. Furthermore, Galmés et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although both genotypes presented similar reductions in π o under water shortage conditions, elastic modifications were of higher relevance in the LSL genotype (Figure 1 ). In fact, ε adjustments occurring under water deficit stress are variable (see, for instance, Sobrado & Turner, 1983 ; Lo Gullo & Salleo, 1988 ; Nadal et al., 2020 ; Roig‐Oliver, Bresta, Nadal, et al., 2020 ; Roig‐Oliver, Nadal, Bota, et al., 2020 ; Roig‐Oliver, Nadal, Clemente‐Moreno, et al., 2020 ; Roig‐Oliver, Fullana‐Pericàs, et al., 2021 ), suggesting that they could be species‐dependent. Furthermore, Galmés et al.…”
Section: Discussionmentioning
confidence: 99%
“…An extended experimental design of the previous experiment showed that pectins and hemicelluloses were significantly modified after only 5 and 24 h of rewatering, respectively, preceded by a long‐term water deprivation (Roig‐Oliver, Bresta, et al., 2021 ). Together with the results observed in other species, it has been proposed that changes in cell wall composition of mature leaves during abiotic stresses application could regulate g m and/or ε adjustments in a species‐dependent way (Clemente‐Moreno et al., 2019 ; Roig‐Oliver, Bresta, et al., 2021 ; Roig‐Oliver, Fullana‐Pericàs, et al., 2021 ; Roig‐Oliver, Bresta, Nadal, et al., 2020 ; Roig‐Oliver, Nadal, Bota, et al., 2020 ; Roig‐Oliver, Nadal, Clemente‐Moreno, et al., 2020 ). Interestingly, here we show that the role of the cell wall composition in determining these functional traits differs even between different genotypes of the same species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that even a slight drought (up to 12 days) caused an increase in lignin precursors (coumaric and caffeic acids) in xylem maize juice, and this was due to a decrease in anionic peroxidase activity, indicating the effect of drought on lignin biosynthesis [49]. Roig-Oliver et al showed for the first time that during long-term water deficiency, changes in the content of lignin, cellulose and hemicellulose in the cell walls of Helianthus annuus were accompanied by a significant decrease in phenols associated with the wall (coumaric, ferulic and caffeic acids) and with a negative correlation with photosynthesis (conductivity of the mesophyll to CO 2 ), and with a positive correlation with palisade mesophyll thickness [52,53].…”
Section: Role Of Lignin Pectin and Cellulosementioning
confidence: 99%